STAGES OF DEVELOPMENT OF INTERNET TECHNOLOGIES IN ELECTION CAMPAIGNS IN RUSSIA - Ekaterina Olegovna Kiseleva (Вестник Северо-Кавказского федерального университета)
This article is devoted to the stages of development of Internet technologies in election campaigns in Russia. The author gives a classification of electoral cycles based on the use the Internet technology.